Conceptualizing cycling experience in urban design research: a systematic literature review. Issue 1 (2nd January 2021) - Liu, George; Krishnamurthy, Sukanya; van Wesemael, Pieter
ABSTRACT: By conceptualizing a link between the cycling experience and the associated methods in understanding the former, the perspective of a cyclist is highlighted as an opportunity for research in urban design. A systematic review of 20 empirical papers across a variety of disciplines covering both walking and cycling experiences was conducted. This paper links social, sensory and spatial experiences, and connects these experiences to textual, visual and evaluative methodologies. This paper proposes how cycling can be considered in design research; it also provides an insight into how various methods enhance our understanding of cyclists and their surroundings.